(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2020)
Background: In evaluation of non-traumatic subarachnoid hemorrhage CT angiography (CTA) has 97-98% sensitivity and near 100% specificity. Objective: This study was conducted to evaluate the CTA findings of CT positive non traumatic subarachnoid hemorrhage. Methodology: This is an observational cross sectional study performed in Neurology department of National Institute of Neurosciences and Hospital, Dhaka over one year period (January 2019 to December 2019). Total 87 CT positive subarachnoid hemorrhage cases were purposively included in this study. All CT positive patients underwent CTA of Cerebral vessels for further evaluation. The angiography were evaluated by competent neuro-radiologists blinded about the study. Result: Among 87 patients, 40.2% were male and 59.8% were female. The average age was 53.33±11.1 years. Among the studied patient the source of bleeding was found 78.16% aneurysmal and 21.84% non-aneurysmal. 85.30% patients had single aneurysm and 14.70% had multiple aneurysm. The highest number of patient had Acom aneurysm (41.17%) followed by MCA (22.05%), ICA (13.23%), ACA (7.35%) and vertebral artery (1.14%) in order of frequency. Among the multiple aneurysm group most of the patients had combination of Acom, MCA and ICA aneurysm. Conclusion: From this study, we can conclude that CTA can be used as the primary diagnostic tool in evaluation of spontaneous SAH. Journal of National Institute of Neurosciences Bangladesh, 2020;6(2): 78-81